Hepatitis and Liver Cancer: A National Strategy for Prevention and Control of Hepatitis B and C - Institute of Medicine (The National Academies Press, 2010)
The global epidemic of hepatitis B and C is a serious public health problem. Hepatitis B and C are the major causes of chronic liver disease and liver cancer in the world. In the next 10 years, 150,000 people in the United States will die from liver disease or liver cancer associated with chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections. Today, between 800,000 and 1.4 million people in the United States have chronic hepatitis B and between 2.7 and 3.9 million have chronic hepatitis C. People most at risk for hepatitis B and C often are the least likely to have access to medical services. Reducing the rates of illness and death associated with these diseases will require greater awareness and knowledge among health care workers, improved identification of at-risk people, and improved access to medical care. Hepatitis B is a vaccine-preventable disease. Although federal public health officials recommend that all newborns, children, and at-risk adults receive the vaccine, about 46,000 new acute cases of the HBV infection emerge each year, including 1,000 in infants who acquire the infection during birth from their HBV-positive mothers. Unfortunately, there is no vaccine for hepatitis C, which is transmitted by direct exposure to infectious blood. Hepatitis and Liver Cancer identifies missed opportunities related to the prevention and control of HBV and HCV infections. The book presents ways to reduce the numbers of new HBV and HCV infections and the morbidity and mortality related to chronic viral hepatitis. It identifies priorities for research, policy, and action geared toward federal, state, and local public health officials, stakeholder, and advocacy groups and professional organizations.
Keywords: Health and Medicine

Relieving Pain in America: A Blueprint for Transforming Prevention, Care, Education, and Research - Institute of Medicine (The National Academies Press, 2011)
Chronic pain costs the nation up to $635 billion each year in medical treatment and lost productivity. The 2010 Patient Protection and Affordable Care Act required the Department of Health and Human Services (HHS) to enlist the Institute of Medicine (IOM) in examining pain as a public health problem. In this report, the IOM offers a blueprint for action in transforming prevention, care, education, and research, with the goal of providing relief for people with pain in America. To reach the vast multitude of people with various types of pain, the nation must adopt a population-level prevention and management strategy. The IOM recommends that HHS develop a comprehensive plan with specific goals, actions, and timeframes. Better data are needed to help shape efforts, especially on the groups of people currently underdiagnosed and undertreated, and the IOM encourages federal and state agencies and private organizations to accelerate the collection of data on pain incidence, prevalence, and treatments. Because pain varies from patient to patient, healthcare providers should increasingly aim at tailoring pain care to each person's experience, and self-management of pain should be promoted. In addition, because there are major gaps in knowledge about pain across health care and society alike, the IOM recommends that federal agencies and other stakeholders redesign education programs to bridge these gaps. Pain is a major driver for visits to physicians, a major reason for taking medications, a major cause of disability, and a key factor in quality of life and productivity. Given the burden of pain in human lives, dollars, and social consequences, relieving pain should be a national priority.
Keywords: Health and Medicine

Depression in Parents, Parenting, and Children: Opportunities to Improve Identification, Treatment, and Prevention - National Research Council; Institute of Medicine (The National Academies Press, 2009)
Depression is a widespread condition affecting approximately 7.5 million parents in the U.S. each year and may be putting at least 15 million children at risk for adverse health outcomes. Based on evidentiary studies, major depression in either parent can interfere with parenting quality and increase the risk of children developing mental, behavioral and social problems. Depression in Parents, Parenting, and Children highlights disparities in the prevalence, identification, treatment, and prevention of parental depression among different sociodemographic populations. It also outlines strategies for effective intervention and identifies the need for a more interdisciplinary approach that takes biological, psychological, behavioral, interpersonal, and social contexts into consideration. A major challenge to the effective management of parental depression is developing a treatment and prevention strategy that can be introduced within a two-generation framework, conducive for parents and their children. Thus far, both the federal and state response to the problem has been fragmented, poorly funded, and lacking proper oversight. This study examines options for widespread implementation of best practices as well as strategies that can be effective in diverse service settings for diverse populations of children and their families. The delivery of adequate screening and successful detection and treatment of a depressive illness and prevention of its effects on parenting and the health of children is a formidable challenge to modern health care systems. This study offers seven solid recommendations designed to increase awareness about and remove barriers to care for both the depressed adult and prevention of effects in the child. The report will be of particular interest to federal health officers, mental and behavioral health providers in diverse parts of health care delivery systems, health policy staff, state legislators, and the general public.
Keywords: Health and Medicine; Behavioral and Social Sciences

No Time to Lose: Getting More from HIV Prevention - Institute of Medicine (The National Academies Press, 2001)
The United States has spent two productive decades implementing a variety of prevention programs. While these efforts have slowed the rate of infection, challenges remain. The United States must refocus its efforts to contain the spread of HIV and AIDS in a way that would prevent as many new HIV infections as possible. No Time to Lose presents the Institute of Medicine’s framework for a national prevention strategy.
Keywords: Health and Medicine

Cross-Sector Responses to Obesity: Models for Change: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Obesity affects 17 percent of children and adolescents and almost 36 percent of adults in the United States. Conservative estimates suggest that obesity now accounts for almost 20 percent of national health care spending. Until the obesity epidemic is reversed, obesity will continue to drive rates of chronic diseases such as heart disease, stroke, type 2 diabetes, and certain types of cancer. Cross-Sector Responses to Obesity is a summary of a workshop convened by the Institute of Medicine Roundtable on Obesity Solutions in September 2014 to explore models of cross-sector work that may reduce the prevalence and consequences of obesity. This report identifies case studies of cross-sector initiatives that engage partners from diverse fields, and lessons learned from and barriers to established cross-sector initiatives.
Keywords: Food and Nutrition; Health and Medicine

Cross-Sector Responses to Obesity: Models for Change: Workshop in Brief - Institute of Medicine (The National Academies Press, 2014)
On September 30, 2014, the Institute of Medicine's Roundtable on Obesity Solutions held a 1-day workshop titled "Cross-Sector Work on Obesity Prevention, Treatment, and Weight Maintenance: Models for Change." The workshop was designed to explore models of cross-sector work that may reduce the prevalence and consequences of obesity, discuss lessons learned from case studies of cross-sector initiatives, and spur future cross-sector collaboration. This brief summary of the workshop highlights the salient points that emerged from the presentations and discussions at the workshop.
Keywords: Food and Nutrition

The Hidden Epidemic: Confronting Sexually Transmitted Diseases - Institute of Medicine (The National Academies Press, 1997)
The United States has the dubious distinction of leading the industrialized world in overall rates of sexually transmitted diseases (STDs), with 12 million new cases annually. About 3 million teenagers contract an STD each year, and many will have long-term health problems as a result. Women and adolescents are particularly vulnerable to these diseases and their health consequences. In addition, STDs increase the risk of HIV transmission. The Hidden Epidemic examines the scope of sexually transmitted infections in the United States and provides a critical assessment of the nation's response to this public health crisis. The book identifies the components of an effective national STD prevention and control strategy and provides direction for an appropriate response to the epidemic. Recommendations for improving public awareness and education, reaching women and adolescents, integrating public health programs, training health care professionals, modifying messages from the mass media, and supporting future research are included. The book documents the epidemiological dimensions and the economic and social costs of STDs, describing them as "a secret epidemic" with tremendous consequences. The committee frankly discusses the confusing and often hypocritical nature of how Americans deal with issues regarding sexuality—the conflicting messages conveyed in the mass media, the reluctance to promote condom use, the controversy over sex education for teenagers, and the issue of personal blame. The Hidden Epidemic identifies key elements of effective, culturally appropriate programs to promote healthy behavior by adolescents and adults. It examines the problem of fragmentation in STD services and provides examples of communities that have formed partnerships between stakeholders to develop integrated approaches. The committee's recommendations provide a practical foundation on which to build an integrated national program to help young people and adults develop habits of healthy sexuality. The Hidden Epidemic was written for both health care professionals and people without a medical background and will be indispensable to anyone concerned about preventing and controlling STDs.
Keywords: Health and Medicine

Bringing Public Health into Urban Revitalization: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
On November 10, 2014, the Roundtable on Environmental Health Sciences, Research, and Medicine held a 1-day workshop titled "Bringing Public Health into Urban Revitalization." The purpose of the workshop was to explore public health issues related to the redesign of major U.S. cities, focusing on recent examples from Detroit, Michigan; New York City; and Washington, DC. Workshop speakers showed how rebuilding efforts provide an opportunity to reimagine the built environment, increase a sense of community, increase the role of public health departments and health systems, and increase the use of green technologies.
Keywords: Health and Medicine

Community Violence as a Population Health Issue: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In June 2016 the National Academies of Sciences, Engineering, and Medicine held a workshop on public health approaches to reducing and preventing community violence. Participants discussed the effects of trauma and violence on communities and explored approaches that communities and multi-sector partners are using to build safe, resilient, and healthy communities. They also explored community- and hospital-based anti-violence programs, community policing, blight reduction, and the community’s participation in initiatives, including the youth and adults at risk or responsible for much of the violence in communities. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Roundtable on Obesity Solutions of the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, on September 27, 2016, titled "Driving Action and Progress on Obesity Prevention and Treatment." The workshop was designed to (1) review the progress that has been made in obesity prevention and treatment; (2) identify some of the levers that can drive significant future progress; and (3) discuss how gaps in the field can be filled. This Proceedings of a Workshop-in Brief highlights key points made during the presentations and discussions and is not intended to provide a comprehensive summary of information shared during the workshop.
Keywords: Food and Nutrition

Integrating Firearm Injury Prevention into Health Care: Proceedings of a Joint Workshop of the National Academies of Sciences, Engineering, and Medicine; Northwell Health; and PEACE Initiative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The staggering number of deaths and emergency department visits caused by firearm injuries has only grown with time. Costs associated with firearm related injuries amount to over a billion dollars annually in the United States alone, not including physician charges and postdischarge costs. To address this epidemic, in April of 2022, the National Academies of Sciences, Engineering, and Medicine's Board on Population Health and Public Health Practice, in collaboration with Northwell Heath and the PEACE Initiative, brought together firearm injury prevention thought leaders to explore how health systems can integrate interventions for firearm injury prevention into routine care for the purpose of improving the health of patients and communities. The workshop speakers discussed strategies for firearm injury and mortality prevention and its integration into routine care. Speakers also explored facilitators and barriers to implementation strategies, and how health systems might work to overcome those barriers.
Keywords: Health and Medicine

Joint U.S.-Mexico Workshop on Preventing Obesity in Children and Youth of Mexican Origin: Summary - Institute of Medicine (The National Academies Press, 2007)
The Joint U.S.-Mexico Workshop on Preventing Obesity in Children and Youth of Mexican Origin was initiated by a desire to share experiences regarding the problem of obesity in children and youth of Mexican origin on both sides of the border, with a particular focus on potential solutions. U.S and Mexican researchers, public health officials, industry leaders, and policy-makers engaged in valuable dialogue to share perspectives, challenges, and opportunities. Commonalities and differences in the United States and Mexico regarding risk factors, potential interventions and programs, and need for all sectors to collaborate and make progress toward solving this serious public health problem were also discussed. This dialogue served as a basis to explore a bi-national agenda for addressing this epidemic, which was the ultimate goal of the workshop.
Keywords: Health and Medicine

Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation - Institute of Medicine (The National Academies Press, 2012)
One-third of adults are now obese, and children's obesity rates have climbed from 5 to 17 percent in the past 30 years. The causes of the nation's obesity epidemic are multi-factorial, having much more to do with the absence of sidewalks and the limited availability of healthy and affordable foods than a lack of personal responsibility. The broad societal changes that are needed to prevent obesity will inevitably affect activity and eating environments and settings for all ages. Many aspects of the obesity problem have been identified and discussed; however, there has not been complete agreement on what needs to be done to accelerate progress. Accelerating Progress in Obesity Prevention reviews previous studies and their recommendations and presents five key recommendations to accelerate meaningful change on a societal level during the next decade. The report suggests recommendations and strategies that, independently, can accelerate progress, but urges a systems approach of many strategies working in concert to maximize progress in accelerating obesity prevention. The recommendations in Accelerating Progress in Obesity Prevention include major reforms in access to and opportunities for physical activity; widespread reductions in the availability of unhealthy foods and beverages and increases in access to healthier options at affordable, competitive prices; an overhaul of the messages that surround Americans through marketing and education with respect to physical activity and food consumption; expansion of the obesity prevention support structure provided by health care providers, insurers, and employers; and schools as a major national focal point for obesity prevention. The report calls on all individuals, organizations, agencies, and sectors that do or can influence physical activity and nutrition environments to assess and begin to act on their potential roles as leaders in obesity prevention.
Keywords: Food and Nutrition; Health and Medicine

Strategies for Developing, Implementing, and Sustaining Sexual Harassment Bystander Intervention Programs for Faculty, Staff, and Graduate Students - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
To address the persistent problem of sexual harassment within higher education, research suggests that environments need to convey that sexual harassment is not a norm and actively discourage it when it does occur. One approach that researchers have identified as helping to create such environments is bystander intervention programs, which prepare and equip individuals to interrupt and intervene when harassing behavior occurs. This paper explores bystander intervention training approaches that are designed for the complex work environments within higher education, and considers how to apply the principles of bystander intervention to the experiences and environments of faculty, staff, and graduate students., Institutions within the Action Collaborative were asked a standard set of questions to learn about their experiences with commitment and buy-in from leadership, details on how the trainings were developed and what audience it was targeted to, and how the training programs were evaluated. The paper summarizes responses from seven of these institutions and ends with a call for additional research and action. This individually-authored issue paper was created by members of the Prevention Working Group of the Action Collaborative on Preventing Sexual Harassment in Higher Education to understand how institutions are addressing the gap in bystander intervention training for faculty, staff, and graduate students. The Action Collaborative on Preventing Sexual Harassment in Higher Education of the National Academies of Sciences, Engineering, and Medicine brings together academic and research institutions and key stakeholders to work toward targeted, collective action on addressing and preventing sexual harassment across all disciplines and among all people in higher education. The Action Collaborative includes four working groups (Prevention, Response, Remediation, and Evaluation) that identify topics in need of research, gather information, and publish resources for the higher education community.
Keywords: Education

Primary Care and Public Health: Exploring Integration to Improve Population Health - Institute of Medicine (The National Academies Press, 2012)
Ensuring that members of society are healthy and reaching their full potential requires the prevention of disease and injury; the promotion of health and well-being; the assurance of conditions in which people can be healthy; and the provision of timely, effective, and coordinated health care. Achieving substantial and lasting improvements in population health will require a concerted effort from all these entities, aligned with a common goal. The Health Resources and Services Administration (HRSA) and the Centers for Disease Control and Prevention (CDC) requested that the Institute of Medicine (IOM) examine the integration of primary care and public health. Primary Care and Public Health identifies the best examples of effective public health and primary care integration and the factors that promote and sustain these efforts, examines ways by which HRSA and CDC can use provisions of the Patient Protection and Affordable Care Act to promote the integration of primary care and public health, and discusses how HRSA-supported primary care systems and state and local public health departments can effectively integrate and coordinate to improve efforts directed at disease prevention. This report is essential for all health care centers and providers, state and local policy makers, educators, government agencies, and the public for learning how to integrate and improve population health.
Keywords: Health and Medicine

Growing Up Tobacco Free: Preventing Nicotine Addiction in Children and Youths - Institute of Medicine (The National Academies Press, 1994)
Tobacco use kills more people than any other addiction and we know that addiction starts in childhood and youth. We all agree that youths should not smoke, but how can this be accomplished? What prevention messages will they find compelling? What effect does tobacco advertising—more than $10 million worth every day—have on youths? Can we responsibly and effectively restrict their access to tobacco products? These questions and more are addressed in Growing Up Tobacco Free, prepared by the Institute of Medicine to help everyone understand the troubling issues surrounding youths and tobacco use. Growing Up Tobacco Free provides a readable explanation of nicotine's effects and the process of addiction, and documents the search for an effective approach to preventing the use of cigarettes, chewing and spitting tobacco, and snuff by children and youths. It covers the results of recent initiatives to limit young people's access to tobacco and discusses approaches to controls or bans on tobacco sales, price sensitivity among adolescents, and arguments for and against taxation as a prevention strategy for tobacco use. The controversial area of tobacco advertising is thoroughly examined. With clear guidelines for public action, everyone can benefit by reading and acting on the messages in this comprehensive and compelling book.
Keywords: Health and Medicine

Population Health Implications of the Affordable Care Act: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Population Health Implications of the Affordable Care Act is the summary of a workshop convened in June 2013 by the Institute of Medicine Roundtable on Population Health Improvement to explore the likely impact on population health improvement of various provisions within the Affordable Care Act (ACA). This public workshop featured presentations and discussion of the impact of various provisions in the ACA on population health improvement. Several provisions of the ACA offer an unprecedented opportunity to shift the focus of health experts, policy makers, and the public beyond health care delivery to the broader array of factors that play a role in shaping health outcomes. The shift includes a growing recognition that the health care delivery system is responsible for only a modest proportion of what makes and keeps Americans healthy and that health care providers and organizations could accept and embrace a richer role in communities, working in partnership with public health agencies, community-based organizations, schools, businesses, and many others to identify and solve the thorny problems that contribute to poor health. Population Health Implications of the Affordable Care Act looks beyond narrow interpretations of population as the group of patients covered by a health plan to consider a more expansive understanding of population, one focused on the distribution of health outcomes across all individuals living within a certain set of geopolitical boundaries. In establishing the National Prevention, Health Promotion, and Public Health Council, creating a fund for prevention and public health, and requiring nonprofit hospitals to transform their concept of community benefit, the ACA has expanded the arena for interventions to improve health beyond the "doctor's" office. Improving the health of the population - whether in a community or in the nation as a whole - requires acting to transform the places where people live, work, study, and play. This report examines the population health-oriented efforts of and interactions among public health agencies (state and local), communities, and health care delivery organizations that are beginning to facilitate such action.
Keywords: Health and Medicine

Preventing HIV Transmission: The Role of Sterile Needles and Bleach - Institute of Medicine (The National Academies Press, 1995)
This volume addresses the interface of two major national problems: the epidemic of HIV-AIDS and the widespread use of illegal injection drugs. Should communities have the option of giving drug users sterile needles or bleach for cleaning needs in order to reduce the spread of HIV? Does needle distribution worsen the drug problem, as opponents of such programs argue? Do they reduce the spread of other serious diseases, such as hepatitis? Do they result in more used needles being carelessly discarded in the community? The panel takes a critical look at the available data on needle exchange and bleach distribution programs, reaches conclusions about their efficacy, and offers concrete recommendations for public policy to reduce the spread of HIV/AIDS. The book includes current knowledge about the epidemiologies of HIV/AIDS and injection drug use; characteristics of needle exchange and bleach distribution programs and views on those programs from diverse community groups; and a discussion of laws designed to control possession of needles, their impact on needle sharing among injection drug users, and their implications for needle exchange programs.
Keywords: Health and Medicine

Vital Signs: Core Metrics for Health and Health Care Progress - Institute of Medicine (The National Academies Press, 2015)
Thousands of measures are in use today to assess health and health care in the United States. Although many of these measures provide useful information, their usefulness in either gauging or guiding performance improvement in health and health care is seriously limited by their sheer number, as well as their lack of consistency, compatibility, reliability, focus, and organization. To achieve better health at lower cost, all stakeholders - including health professionals, payers, policy makers, and members of the public - must be alert to what matters most. What are the core measures that will yield the clearest understanding and focus on better health and well-being for Americans? Vital Signs explores the most important issues - healthier people, better quality care, affordable care, and engaged individuals and communities - and specifies a streamlined set of 15 core measures. These measures, if standardized and applied at national, state, local, and institutional levels across the country, will transform the effectiveness, efficiency, and burden of health measurement and help accelerate focus and progress on our highest health priorities. Vital Signs also describes the leadership and activities necessary to refine, apply, maintain, and revise the measures over time, as well as how they can improve the focus and utility of measures outside the core set. If health care is to become more effective and more efficient, sharper attention is required on the elements most important to health and health care. Vital Signs lays the groundwork for the adoption of core measures that, if systematically applied, will yield better health at a lower cost for all Americans.
Keywords: Health and Medicine

Child and Adolescent Health and Health Care Quality: Measuring What Matters - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Increasing public investments in health care services for low-income and special needs children and adolescents in the United States have raised questions about whether these efforts improve their health outcomes. Yet it is difficult to assess the general health status and health care quality for younger populations, especially those at risk of poor health outcomes, because the United States has no national information system that can provide timely, comprehensive, and reliable indicators in these areas for children and adolescents. Without such a system in place, it is difficult to know whether and how selected health care initiatives and programs contribute to children's health status. Child and Adolescent Health and Health Care Quality identifies key advances in the development of pediatric health and health care quality measures, examines the capacity of existing federal data sets to support these measures, and considers related research activities focused on the development of new measures to address current gaps. This book posits the need for a comprehensive strategy to make better use of existing data, to integrate different data sources, and to develop new data sources and collection methods for unique populations. Child and Adolescent Health and Health Care Quality looks closely at three areas: the nature, scope, and quality of existing data sources; gaps in measurement areas; and methodological areas that deserve attention. Child and Adolescent Health and Health Care Quality makes recommendations for improving and strengthening the timeliness, quality, public transparency, and accessibility of information on child health and health care quality. This book will be a vital resource for health officials at the local, state, and national levels, as well as private and public health care organizations and researchers.
Keywords: Health and Medicine

Integrating Health Literacy, Cultural Competence, and Language Access Services: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The aging and evolving racial and ethnic composition of the U.S. population has the United States in the midst of a profound demographic shift and health care organizations face many issues as they move to address and adapt to this change. In their drive to adequately serve increasingly diverse communities, health care organizations are searching for approaches that will enable them to provide information and service to all persons, regardless of age, race, cultural background, or language skills, in a manner that facilitates understanding and use of that information to make appropriate health decisions. To better understand how the dynamic forces operating in health care today impact the delivery of services in a way that is health literate, culturally competent, and in an appropriate language for patients and their families, the National Academies of Sciences, Engineering, and Medicine conducted a public workshop on the integration of health literacy, cultural competency, and language access services. Participants discussed skills and competencies needed for effective health communication, including health literacy, cultural competency, and language access services; interventions and strategies for integration; and differing perspectives such as providers and systems, patients and families, communities, and payers. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Suicide Prevention and Intervention: Summary of a Workshop - Institute of Medicine (The National Academies Press, 2001)
For many, thoughts of suicide are abundant and frequent. There exists a fear of death but an even greater fear of life due to the latter's hardships. Participants of the committee on the Pathophysiology and Prevention of Adult and Adolescent Suicide of the Institute of Medicine's workshop on suicide prevention; however, believe that there is potential for better suicide prevention. Two workshops were convened by the committee: Risk Factors for Suicide, March 14, 2001 and Suicide Prevention and Intervention, May 14, 2001. The two workshops were designed to allow invited presenters to share with the committee and other workshop participants their particular expertise in suicide, and to discuss and examine the existing knowledge base. Participants of the second workshop were selected to represent many areas including: design and analysis of prevention programs, suicide contagion, and firearm availability and suicide. The committee wanted to assess the science base of suicide etiology, evaluate the current status of suicide prevention, and examine current strategies for the study of suicide. Suicide Prevention and Intervention: Summary of a Workshop summarizes the major themes that arose during the workshop. It also includes the workshop agenda and a list of speakers that were present.
Keywords: Health and Medicine

Health Systems Interventions to Prevent Firearm Injuries and Death: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Firearm injuries and death are a serious public health concern in the United States. Firearm-related injuries account for tens of thousands of premature deaths of adults and children each year and significantly increase the burden of injury and disability. Firearm injuries are also costly to the health system, accounting for nearly $3 billion in emergency department and inpatient care each year. The National Academies of Sciences, Engineering, and Medicine convened a workshop to examine the roles that health systems can play in addressing the epidemic of firearm violence in the United States. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Information and Communication Technology and Peacebuilding: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2008)
Those who would use information and communication technology (ICT) in the cause of peace need to be cognizant of the risks as well as the benefits. ICT can facilitate positive dialogue but also hate speech. It can be used to fight corruption but also facilitate it. Simply giving people more information does not necessarily lead to predictable or positive results. As people become more informed, they may become more motivated to change their circumstances and to do so violently. On December 14, 2007, the National Academy of Engineering (NAE) convened a group of experts in diverse fields to consider the role of ICT in promoting peace and conflict resolution. The one-day workshop was designed to consider current and emerging technologies and strategies for employing them in conflict management and diplomacy. It also aimed to explore how organizations with a role in promoting peace, like the U.S. Institute of Peace, can most effectively leverage technology in carrying out their missions. Information and Communication Technology and Peacebuilding: Summary of a Workshop reviews the group's discussions on number of key issues, illuminates certain practitioner needs, and suggests possible next steps.
Keywords: Computers and Information Technology

The Hidden Epidemic: Confronting Sexually Transmitted Diseases, Summary - Institute of Medicine (The National Academies Press, 1997)
Committee on Prevention and Control of Sexually Transmitted Diseases (1997, 68 pp.; $4.00 each; minimum order of 50 copies).
Keywords: Health and Medicine

Substance Use Disorders in the U.S. Armed Forces - Institute of Medicine (The National Academies Press, 2013)
Problems stemming from the misuse and abuse of alcohol and other drugs are by no means a new phenomenon, although the face of the issues has changed in recent years. National trends indicate substantial increases in the abuse of prescription medications. These increases are particularly prominent within the military, a population that also continues to experience long-standing issues with alcohol abuse. The problem of substance abuse within the military has come under new scrutiny in the context of the two concurrent wars in which the United States has been engaged during the past decade—in Afghanistan (Operation Enduring Freedom) and Iraq (Operation Iraqi Freedom and Operation New Dawn). Increasing rates of alcohol and other drug misuse adversely affect military readiness, family readiness, and safety, thereby posing a significant public health problem for the Department of Defense (DoD). To better understand this problem, DoD requested that the Institute of Medicine (IOM) assess the adequacy of current protocols in place across DoD and the different branches of the military pertaining to the prevention, screening, diagnosis, and treatment of substance use disorders (SUDs). Substance Use Disorders in the U.S. Armed Forces reviews the IOM's task of assessing access to SUD care for service members, members of the National Guard and Reserves, and military dependents, as well as the education and credentialing of SUD care providers, and offers specific recommendations to DoD on where and how improvements in these areas could be made.
Keywords: Health and Medicine; Conflict and Security Issues

Disability in America: Toward a National Agenda for Prevention - Institute of Medicine (The National Academies Press, 1991)
Disability in America presents a five-prong strategy for reducing the incidence and prevalence of disability as well as its personal, social, and economic consequences. Although the preferred goal is to avoid potentially disabling conditions, the authoring committee focuses on the need to prevent or reverse the progression that leads to disability and reduced quality of life in persons with potentially disabling conditions. Calling for a coherent national program to focus on prevention, the committee sets forth specific recommendations for federal agencies, state and local programs, and the private sector. This comprehensive agenda addresses the need for improved methods for collecting disability data, specific research questions, directions for university training, reform in insurance coverage, prenatal care, vocational training, and a host of other arenas for action.
Keywords: Health and Medicine

Opportunities to Promote Children's Behavioral Health: Health Care Reform and Beyond: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The Patient Protection and Affordable Care Act (ACA), which was signed into law in 2010, has several provisions that could greatly improve the behavioral health of children and adolescents in the United States. It requires that many insurance plans cover mental health and substance use disorder services, rehabilitative services to help support people with behavioral health challenges, and preventive services like behavioral assessments for children and depression screening for adults. These and other provisions provide an opportunity to confront the many behavioral health challenges facing youth in America. To explore how the ACA and other aspects of health care reform can support innovations to improve children's behavioral health and sustain those innovations over time, the Forum on Promoting Children's Cognitive, Affective, and Behavioral Health held a workshop on April 1-2, 2015. The workshop explicitly addressed the behavioral health needs of all children, including those with special health needs. It also took a two-generation approach, looking at the programs and services that support not only children but also parents and families. This report summarizes the presentations and discussions of this workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Local Government Actions to Prevent Childhood Obesity - Transportation Research Board; Institute of Medicine; National Research Council (The National Academies Press, 2009)
The prevalence of childhood obesity is so high in the United States that it may reduce the life expectancy of today's generation of children. While parents and other adult caregivers play a fundamental role in teaching children about healthy behaviors, even the most positive efforts can be undermined by local environments that are poorly suited to supporting healthy behaviors. For example, many communities lack ready sources of healthy food choices, such as supermarkets and grocery stores. Or they may not provide safe places for children to walk or play. In such communities, even the most motivated child or adolescent may find it difficult to act in healthy ways. Local governments—with jurisdiction over many aspects of land use, food marketing, community planning, transportation, health and nutrition programs, and other community issues—are ideally positioned to promote behaviors that will help children and adolescents reach and maintain healthy weights. Local Government Actions to Prevent Childhood Obesity presents a number of recommendations that touch on the vital role of government actions on all levels—federal, state, and local—in childhood obesity prevention. The book offers healthy eating and physical activity strategies for local governments to consider, making it an excellent resource for mayors, managers, commissioners, council members, county board members, and administrators.
Keywords: Health and Medicine; Food and Nutrition

Priorities for Research to Reduce the Threat of Firearm-Related Violence - Institute of Medicine; National Research Council (The National Academies Press, 2013)
In 2010, more than 105,000 people were injured or killed in the United States as the result of a firearm-related incident. Recent, highly publicized, tragic mass shootings in Newtown, CT; Aurora, CO; Oak Creek, WI; and Tucson, AZ, have sharpened the American public's interest in protecting our children and communities from the harmful effects of firearm violence. While many Americans legally use firearms for a variety of activities, fatal and nonfatal firearm violence poses a serious threat to public safety and welfare. In January 2013, President Barack Obama issued 23 executive orders directing federal agencies to improve knowledge of the causes of firearm violence, what might help prevent it, and how to minimize its burden on public health. One of these orders directed the Centers for Disease Control and Prevention (CDC) to, along with other federal agencies, immediately begin identifying the most pressing problems in firearm violence research. The CDC and the CDC Foundation asked the IOM, in collaboration with the National Research Council, to convene a committee tasked with developing a potential research agenda that focuses on the causes of, possible interventions to, and strategies to minimize the burden of firearm-related violence. Priorities for Research to Reduce the Threat of Firearm-Related Violence focuses on the characteristics of firearm violence, risk and protective factors, interventions and strategies, the impact of gun safety technology, and the influence of video games and other media.
Keywords: Behavioral and Social Sciences; Health and Medicine

Strategies for Scaling Effective Family-Focused Preventive Interventions to Promote Children's Cognitive, Affective, and Behavioral Health: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Over the last three decades, researchers have made remarkable progress in creating and testing family-focused programs aimed at fostering the cognitive, affective, and behavioral health of children. These programs include universal interventions, such as those for expecting or new parents, and workshops for families whose children are entering adolescence, as well as programs targeted to especially challenged parents, such as low-income single teens about to have their first babies, or the parents of children with autism. Some family-focused programs have been shown to foster significantly better outcomes in children, including enhanced educational performance, and reduced rates of teen pregnancy, substance abuse, and child conduct and delinquency, as well as reduced child abuse. The favorable cost-benefit ratios of some of these programs are due, in part, to the multiple and far-ranging effects that family-focused prevention programs targeting children can have. Other family-focused programs have shown success in smaller academic studies but have not been widely applied, or have not worked as effectively or failed when applied to more diverse real-world settings. Strategies for Scaling Effective Family-Focused Preventive Interventions to Promote Children's Cognitive, Affective, and Behavioral Health is the summary of a workshop convened by the Institute of Medicine Forum on Promoting Children's Cognitive, Affective, and Behavioral Health to explore effective preventive interventions for youth that can modify risk and promote protective factors that are linked to mental, emotional, and behavioral health, and how to apply this existing knowledge. Based on the 2009 report Preventing Mental, Emotional, and Behavioral Disorders Among Young People, this report considers how to build a stronger research and practice base around the development and implementation of programs, practices, and policies that foster children's health and well-being across the country, while engaging multi-sectorial stakeholders. While research has advanced understanding of risk, promotive, and protective factors in families that influence the health and well-being of youth, a challenge remains to provide family-focused interventions across child and adolescent development at sufficient scale and reach to significantly reduce the incidence and prevalence of negative cognitive, affective, and behavioral outcomes in children and adolescents nationwide, as well as to develop widespread demand for effective programs by end users. This report explores new and innovative ways to broaden the reach and demand for effective programs and to generate alternative paradigms for strengthening families.
Keywords: Health and Medicine; Behavioral and Social Sciences

Community Interventions to Prevent Veteran Suicide: The Role of Social Determinants: Proceedings of a Virtual Symposium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On March 28 and 29, 2022, the Board on Behavioral, Cognitive, and Sensory Sciences at the National Academies of Sciences, Engineering, and Medicine held a virtual symposium entitled Community Interventions to Prevent Veteran Suicide: The Role of Social Determinants to gain a better understanding of social determinants influencing the recent increase in suicide risk and how currently available practice guidelines can inform community-level preventive interventions, particularly those targeting veteran populations. Presenters and participants explored the relevant social, cultural, and economic factors driving changes in suicide risk among veterans and ways that current best practices for suicide prevention and treatment can be applied at the community level. This publication summarizes the presentations and discussion of the symposium.
Keywords: Health and Medicine; Behavioral and Social Sciences

Methadone Treatment for Opioid Use Disorder: Improving Access Through Regulatory and Legal Change: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Methadone is a Food and Drug Administration- (FDA-) approved medication for treating opioid use disorder (OUD), a chronic brain disease that affects more than 2.7 million people in the United States aged 12 and older. Despite its effectiveness in saving lives, many barriers impede access to, initiation of, and retention in methadone treatment for OUD. To address these barriers, on March 3 and 4, 2022, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on "Methadone Treatment for Opioid Use Disorder: Examining Federal Regulations and Laws," at the request of the Office of National Drug Control Policy in the Executive Office of the President. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Preventing HIV Infection Among Injecting Drug Users in High-Risk Countries: An Assessment of the Evidence - Institute of Medicine (The National Academies Press, 2007)
Drug dependence is a complex, chronic, relapsing condition that is often accompanied by severe health, psychological, economic, legal, and social consequences. Injecting drug users are particularly vulnerable to HIV and other bloodborne infections (such as hepatitis C) as a result of sharing contaminated injecting equipment. All drug-dependent individuals, including injecting drug users (IDUs), may be at increased risk of HIV infection because of high-risk sexual behaviors. There are an estimated 13.2 million injecting drug users (IDUs) world-wide—78 percent of whom live in developing or transitional countries. The sharing of contaminated injecting equipment has become a major driving force of the global AIDS epidemic and is the primary mode of HIV transmission in many countries. In some cases, epidemics initially fueled by the sharing of contaminated injecting equipment are spreading through sexual transmission from IDUs to non-injecting populations, and through perinatal transmission to newborns. Reversing the rise of HIV infections among IDUs has thus become an urgent global public health challenge—one that remains largely unmet. In response to this challenge, the Institute of Medicine convened a public workshop in Geneva in December 2005 to gather information from experts on IDU-driven HIV epidemics in the most affected regions of the world with an emphasis on countries throughout Eastern Europe, the Commonwealth of Independent States, and significant parts of Asia. Experts from other regions also provided information on their experiences in preventing HIV infection among IDUs. This report provides a summary of the workshop discussions. Preventing HIV Infection among Injecting Drug Users in High Risk Countries describes the evidence on the intermediate outcomes of drug-related risk and sex-related risk prior to examining the impact on HIV transmission. This report focuses on programs that are designed to prevent the transmission of HIV among injecting drug users. These programs range from efforts to curtail non-medical drug use to those that encourage reduction in high-risk behavior among drug users. Although the report focuses on HIV prevention for IDUs in high-risk countries, the Committee considered evidence from countries around the world. The findings and recommendations of this report are also applicable to countries where injecting drug use is not the primary driver, but in which injection drug use is nevertheless associated with significant HIV transmission.
Keywords: Health and Medicine

Toward the Prevention of Alcohol Problems: Government, Business, and Community Action - National Research Council (The National Academies Press, 1984)
Keywords: Health and Medicine

The Effects of Drug Control Policies on Individual and Community Health for People of Color: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The United States has a complex system of laws and policies that attempt to regulate the distribution, manufacture, and use of a variety of non-legal drug substances as part of its overall criminal justice system. Laws regarding drug use have disproportionately impacted individuals and communities of color at every step of the journey through the criminal justice system, including arrest, conviction, sentencing, and incarceration. These disparities have clear outcomes for both individual and community health. To examine the effects of drug control policies on the health of individuals and communities of color, the Roundtable on the Promotion of Health Equity held a workshop on October 8, 2018, in Washington, DC. This publication summarizes the presentations and discussions of the workshop.
Keywords: Health and Medicine

Applying a Health Lens to Decision Making in Non-Health Sectors: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Health is influenced by a wide range of factors, many of which fall outside of the health care delivery sector. These determinants of health include, for example, the characteristics of how people live, work, learn, and play. Decision and policy making in areas such as transportation, housing, and education at different levels of government, and in the private sector, can have far-reaching impacts on health. Throughout the United States there has been increasing dialogue on incorporating a health perspective into policies, programs, and projects outside the health field. Applying a Health Lens to Decision Making in Non-Health Sectors is the summary of a workshop convened in September 2013 by the Institute of Medicine Roundtable on Population Health Improvement to foster cross-sectoral dialogue and consider the opportunities for and barriers to improving the conditions for health in the course of achieving other societal objectives (e.g., economic development, efficient public transit). The roundtable engaged members, outside experts, and stakeholders on three core issues: supporting fruitful interaction between primary care and public health; strengthening governmental public health; and exploring community action in transforming the conditions that influence the public's health. This report is a discussion of health in all policies approaches to promote consideration for potential health effects in policy making in many relevant domains, such as education, transportation, and housing.
Keywords: Health and Medicine

Strategies and Interventions to Reduce Suicide: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The persistent trends in suicide necessitate action among mental health care providers and payers, researchers, and community leaders. Health care settings provide an important opportunity for suicide intervention and prevention, but they cannot yet fully manage suicide risk because of a lack of training, knowledge gaps, and reimbursement challenges. School, workplace, and community-based interventions can help reduce the incidence of suicidal behavior, as can better access to care and reduced access to lethal means of suicide. To better understand the strategies to improve access to effective interventions to prevent suicide, the Forum on Mental Health and Substance Use Disorders at the National Academies of Sciences, Engineering, and Medicine hosted a two-part virtual public workshop, Strategies and Interventions to Reduce Suicide, on June 22, 2021, and July 28, 2021. The first webinar examined the scope of the public health problem, discussed implementation of effective approaches for suicide prevention care, and addressed known barriers to health care access. The second webinar focused on building 9-8-8, the new nationwide emergency number designated to the National Suicide Prevention Lifeline. Participants discussed current crisis systems, gaps, challenges, and needs for marginalized populations. This Proceedings of a Workshop summarizes the presentations and discussions that occurred during the workshops.
Keywords: Health and Medicine

Reducing Suicide: A National Imperative - Institute of Medicine (The National Academies Press, 2002)
Every year, about 30,000 people die by suicide in the U.S., and some 650,000 receive emergency treatment after a suicide attempt. Often, those most at risk are the least able to access professional help. Reducing Suicide provides a blueprint for addressing this tragic and costly problem: how we can build an appropriate infrastructure, conduct needed research, and improve our ability to recognize suicide risk and effectively intervene. Rich in data, the book also strikes an intensely personal chord, featuring compelling quotes about people’s experience with suicide. The book explores the factors that raise a person’s risk of suicide: psychological and biological factors including substance abuse, the link between childhood trauma and later suicide, and the impact of family life, economic status, religion, and other social and cultural conditions. The authors review the effectiveness of existing interventions, including mental health practitioners’ ability to assess suicide risk among patients. They present lessons learned from the Air Force suicide prevention program and other prevention initiatives. And they identify barriers to effective research and treatment. This new volume will be of special interest to policy makers, administrators, researchers, practitioners, and journalists working in the field of mental health.
Keywords: Health and Medicine

Innovative Data Science Approaches to Identify Individuals, Populations, and Communities at High Risk for Suicide: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Emerging real-time data sources, together with innovative data science techniques and methods - including artificial intelligence and machine learning - can help inform upstream suicide prevention efforts. Select social media platforms have proactively deployed these methods to identify individual platform users at high risk for suicide, and in some cases may activate local law enforcement, if needed, to prevent imminent suicide. To explore the current scope of activities, benefits, and risks of leveraging innovative data science techniques to help inform upstream suicide prevention at the individual and population level, the Forum on Mental Health and Substance Use Disorders of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop series consisting of three webinars held on April 28, May 12, and June 30, 2022. This Proceedings highlights presentations and discussions from the workshop.
Keywords: Health and Medicine

Preventing Psychological Disorders in Service Members and Their Families: An Assessment of Programs - Institute of Medicine (The National Academies Press, 2014)
Being deployed to a war zone can result in numerous adverse psychological health conditions. It is well documented in the literature that there are high rates of psychological disorders among military personnel serving in Operation Enduring Freedom in Afghanistan and Operation Iraqi Freedom in Iraq as well as among the service members' families. For service members' families, the degree of hardship and negative consequences rises with the amount of the service members' exposure to traumatic or life-altering experiences. Adult and child members of the families of service members who experience wartime deployments have been found to be at increased risk for symptoms of psychological disorders and to be more likely to use mental health services. In an effort to provide early recognition and early intervention that meet the psychological health needs of service members and their families, DOD currently screens for many of these conditions at numerous points during the military life cycle, and it is implementing structural interventions that support the improved integration of military line personnel, non-medical caregivers, and clinicians, such as RESPECT-Mil (Re-engineering Systems of Primary Care Treatment in the Military), embedded mental health providers, and the Patient-Centered Medical Home. Preventing Psychological Disorders in Service Members and Their Families evaluates risk and protective factors in military and family populations and suggests that prevention strategies are needed at multiple levels - individual, interpersonal, institutional, community, and societal - in order to address the influence that these factors have on psychological health. This report reviews and critiques reintegration programs and prevention strategies for PTSD, depression, recovery support, and prevention of substance abuse, suicide, and interpersonal violence.
Keywords: Health and Medicine

Strategic Approach to the Evaluation of Programs Implemented Under the Tom Lantos and Henry J. Hyde U.S. Global Leadership Against HIV/AIDS, Tuberculosis, and Malaria Reauthorization Act of 2008 - Institute of Medicine; National Research Council (The National Academies Press, 2010)
At the request of Congress, the Institute of Medicine (IOM) will evaluate U.S. global programs to address HIV/AIDS. This book outlines the IOM's strategic approach for this evaluation.
Keywords: Health and Medicine

Fulfilling the Potential of Cancer Prevention and Early Detection: An American Cancer Society and Institute of Medicine Symposium - Institute of Medicine; National Research Council (The National Academies Press, 2004)
This report is the summary of a symposium presented by the American Cancer Society (ACS) and the Institute of Medicine (IOM) to further disseminate the conclusions and recommendations of Fulfilling the Potential of Cancer Prevention and Early Detection. This report discusses issues including better support for tobacco and obesity campaigns; coordination of programs; joint approaches with the food industry; the need for an explicit consensus national tobacco and obesity strategy; viewpoints of payers; changing Medicare's approach to prevention; private sector payment programs; improvements in applied research and dissemination of results; better science in programs; problems in modifying medical practice; and conflict between individual choice and policy options.
Keywords: Health and Medicine

Toward Quality Measures for Population Health and the Leading Health Indicators - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Committee on Quality Measures for the Healthy People Leading Health Indicators was charged by the Office of the Assistant Secretary for Health to identify measures of quality for the 12 Leading Health Indicator (LHI) topics and 26 Leading Health Indicators in Healthy People 2020 (HP2020), the current version of the Department of Health and Human Services (HHS) 10-year agenda for improving the nation's health. The scope of work for this project is to use the nine aims for improvement of quality in public health (population-centered, equitable, proactive, health promoting, risk reducing, vigilant, transparent, effective, and efficient) as a framework to identify quality measures for the Healthy People Leading Health Indicators (LHIs). The committee reviewed existing literature on the 12 LHI topics and the 26 Leading Health Indicators. Quality measures for the LHIs that are aligned with the nine aims for improvement of quality in public health will be identified. When appropriate, alignments with the six Priority Areas for Improvement of Quality in Public Health will be noted in the Committee's report. Toward Quality Measures for Population Health and the Leading Health Indicators also address data reporting and analytical capacities that must be available to capture the measures and for demonstrating the value of the measures to improving population health. Toward Quality Measures for Population Health and the Leading Health Indicators provides recommendations for how the measures can be used across sectors of the public health and health care systems. The six priority areas (also known as drivers) are population health metrics and information technology; evidence-based practices, research, and evaluation; systems thinking; sustainability and stewardship; policy; and workforce and education.
Keywords: Health and Medicine

Countering Violent Extremism Through Public Health Practice: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Countering violent extremism consists of various prevention and intervention approaches to increase the resilience of communities and individuals to radicalization toward violent extremism, to provide nonviolent avenues for expressing grievances, and to educate communities about the threat of recruitment and radicalization to violence. To explore the application of health approaches in community-level strategies to countering violent extremism and radicalization, the National Academies of Sciences, Engineering, and Medicine held a public workshop in September 2016. Participants explored the evolving threat of violent extremism and radicalization within communities across America, traditional versus health-centered approaches to countering violent extremism and radicalization, and opportunities for cross-sector and interdisciplinary collaboration and learning among domestic and international stakeholders and organizations. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Preventing Drug Abuse: What Do We Know? - National Research Council (The National Academies Press, 1993)
As the nation's drug crisis has deepened, public and private agencies have invested huge sums of money in prevention efforts. Are the resulting programs effective? What do we need to know to make them more effective? This book provides a comprehensive overview on what we know about drug abuse prevention and its effectiveness, including: Results of a wide range of antidrug efforts. The role and effectiveness of mass media in preventing drug use. A profile of the drug problem, including a look at drug use by different population groups. A review of three major schools of prevention theory--risk factor reduction, developmental change, and social influence. An examination of promising prevention techniques from other areas of health and human services. This volume offers provocative findings on the connection between low self-esteem and drug use, the role of schools, the reality of changing drug use in the population, and more. Preventing Drug Abuse will be indispensable to anyone involved in the search for solutions, including policymakers, anti-drug program developers and administrators, and researchers.
Keywords: Health and Medicine

Proceedings--Workshop on Needle Exchange and Bleach Distribution Programs (The National Academies Press, 1994)
This book reports on research on and experience with needle exchange and bleach distribution programs and their effects on rates of drug use, the behavior of injection drug users, and the spread of HIV and other infectious diseases among injection drug users. It discusses U.S. needle exchange data, international evaluations of needle exchange programs, legal issues and drug paraphernalia laws, evaluation methods, and bleach distribution programs.
Keywords: Health and Medicine

Prevention and Treatment of Alcohol Problems: Research Opportunities - Institute of Medicine (The National Academies Press, 1990)
A thorough examination of nearly everything known about the prevention and treatment of alcohol problems, this volume is directed particularly at people interested in conducting research and at agencies supporting research into the phenomenon of drinking. The book essentially is two volumes in one. The first covers progress and potential in the prevention of alcohol problems, ranging from the predispositions of the individual to the temptations posed by the environment. The second contains a history and appraisal of treatment methods and their costs, including the health consequences of alcohol abuse. A concluding section describes the funding and research policy emphases believed to be necessary for various aspects of research into prevention and treatment.
Keywords: Health and Medicine

Preventing Violence Against Women and Children: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Violence against women and children is a serious public health concern, with costs at multiple levels of society. Although violence is a threat to everyone, women and children are particularly susceptible to victimization because they often have fewer rights or lack appropriate means of protection. In some societies certain types of violence are deemed socially or legally acceptable, thereby contributing further to the risk to women and children. In the past decade research has documented the growing magnitude of such violence, but gaps in the data still remain. Victims of violence of any type fear stigmatization or societal condemnation and thus often hesitate to report crimes. The issue is compounded by the fact that for women and children the perpetrators are often people they know and because some countries lack laws or regulations protecting victims. Some of the data that have been collected suggest that rates of violence against women range from 15 to 71 percent in some countries and that rates of violence against children top 80 percent. These data demonstrate that violence poses a high burden on global health and that violence against women and children is common and universal. Preventing Violence Against Women and Children focuses on these elements of the cycle as they relate to interrupting this transmission of violence. Intervention strategies include preventing violence before it starts as well as preventing recurrence, preventing adverse effects (such as trauma or the consequences of trauma), and preventing the spread of violence to the next generation or social level. Successful strategies consider the context of the violence, such as family, school, community, national, or regional settings, in order to determine the best programs.
Keywords: Health and Medicine

Immunization Safety Review: Hepatitis B Vaccine and Demyelinating Neurological Disorders - Institute of Medicine (The National Academies Press, 2002)
Immunization to protect infants and children from vaccine-preventable diseases is one of the greatest achievements of public health. Immunization is not without risks, however. It is well established, for example, that the oral polio vaccine can on rare occasion cause paralytic polio.The Immunization Safety Review Committee was established by the Institute of Medicine (IOM) to evaluate the available evidence on a series of immunization safety concerns. The committee is charged with examining three immunization safety hypotheses each year during the three-year study period (2001- 2003). While all of the committee members share the view that immunization is generally beneficial, none of them has a vested interest in the specific immunization safety issues that come before the group. In this report, which is the fourth in the series, the committee examines the hypothesis that the hepatitis B vaccine increases the risk for demyelinating disorders of the central or peripheral nervous systems, including multiple sclerosis (MS) and Guillain-Barré syndrome (GBS).
Keywords: Health and Medicine

Improving the Continued Airworthiness of Civil Aircraft: A Strategy for the FAA's Aircraft Certification Service - National Research Council (The National Academies Press, 1998)
As part of the national effort to improve aviation safety, the Federal Aviation Administration (FAA) chartered the National Research Council to examine and recommend improvements in the aircraft certification process currently used by the FAA, manufacturers, and operators.
Keywords: Space and Aeronautics; Transportation and Infrastructure

Community Violence as a Population Health Issue: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 16, 2016, the Roundtable on Population Health Improvement held a workshop at the Lutheran Church of the Good Shepherd in Brooklyn, New York, to explore the influence of trauma and violence on communities. The workshop highlighted examples of community-based organizations using trauma-informed approaches to treat violence and build safe and healthy communities. Presentations showcased examples that can serve as models in different sectors and communities and shared lessons learned. This publication summarizes the presentation and discussion of the event.
Keywords: Health and Medicine

Research on the Health and Wellness of Commercial Truck and Bus Drivers: Summary of an International Conference - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Conference Proceedings on the Web 5: Research on the Health and Wellness of Commercial Truck and Bus Drivers: Summary of an International Conference is the proceedings of a November 2010 conference held in Baltimore, Maryland.The proceedings highlight and document what transpired at the conference; summarize noteworthy issues and gaps in knowledge identified at the conference; and describe suggestions that were discussed there for possible future directions that the transportation health and safety community might pursue in these arenas.
Keywords: Transportation and Infrastructure

Defining and Evaluating In-Home Drug Disposal Systems For Opioid Analgesics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The proper disposal of unused or expired prescription drugs, particularly controlled substances such as opioids, may help to prevent serious risk of nonmedical use or overdose. In June 2023, the National Academies Forum on Drug Discovery, Development, and Translation hosted a hybrid public workshop to examine the scientific merit and practical implementation of drug disposal options to remove opioid analgesics from the home. Workshop participants considered potential strategies for encouraging and assessing the development and efficacy of in-home drug disposal systems that support the public health goal of mitigating the risk of nonmedical use or overdose associated with opioids.
Keywords: Health and Medicine

Violence in Families: Assessing Prevention and Treatment Programs - Rosemary Chalk; Patricia A. King (The National Academies Press, 1998)
Reports of mistreated children, domestic violence, and abuse of elderly persons continue to strain the capacity of police, courts, social services agencies, and medical centers. At the same time, myriad treatment and prevention programs are providing services to victims and offenders. Although limited research knowledge exists regarding the effectiveness of these programs, such information is often scattered, inaccessible, and difficult to obtain. Violence in Families takes the first hard look at the successes and failures of family violence interventions. It offers recommendations to guide services, programs, policy, and research on victim support and assistance, treatments and penalties for offenders, and law enforcement. Included is an analysis of more than 100 evaluation studies on the outcomes of different kinds of programs and services. Violence in Families provides the most comprehensive review on the topic to date. It explores the scope and complexity of family violence, including identification of the multiple types of victims and offenders, who require different approaches to intervention. The book outlines new strategies that offer promising approaches for service providers and researchers and for improving the evaluation of prevention and treatment services. Violence in Families discusses issues that underlie all types of family violence, such as the tension between family support and the protection of children, risk factors that contribute to violent behavior in families, and the balance between family privacy and community interventions. The core of the book is a research-based review of interventions used in three institutional sectors—social services, health, and law enforcement settings—and how to measure their effectiveness in combating maltreatment of children, domestic violence, and abuse of the elderly. Among the questions explored by the committee: Does the child protective services system work? Does the threat of arrest deter batterers? The volume discusses the strength of the evidence and highlights emerging links among interventions in different institutional settings. Thorough, readable, and well organized, Violence in Families synthesizes what is known and outlines what needs to be discovered. This volume will be of great interest to policymakers, social services providers, health care professionals, police and court officials, victim advocates, researchers, and concerned individuals.
Keywords: Behavioral and Social Sciences; Health and Medicine

Science and the National Parks - National Research Council (The National Academies Press, 1992)
The U.S. National Park Service needs much better scientific information to protect the nation's parks for future generations, and research must be an essential element in its mandate. Science and the National Parks examines the reasons why science is important to the national parks, reviews previous evaluations of research in the parks, and recommends ways to improve the current science program. The book stresses the need for two distinct but related approaches to research, called "science for the parks" and "parks for science." Science for the parks includes research to gain understanding of park resources and develop effective management strategies. The parks for science concept recognizes that the national parks are potentially very important to scientific investigations of broad national and global environmental problems and invaluable for understanding the ecological response to anthropogenic change. Science and the National Parks is a critical assessment of the problems hampering the current Park Service science program, providing strong recommendations to help the agency establish a true mandate for science, create separate funding and autonomy for the program, and enhance its credibility and quality.
Keywords: Earth Sciences

Advancing The Principles of The Prevention Through People Program (The National Academies Press, 1997)

Research Briefings 1986 (The National Academies Press, 1986)
Prepared for the Office of Science and Technology Policy and the National Science Foundation, these briefings examine areas important to the progress of U.S. science and technology: the science of interfaces and thin films, decision making and problem solving, protein structure and biological function, and the prevention and treatment of viral diseases.
Keywords: Policy for Science and Technology

Preventing Teen Motor Crashes: Contributions from the Behavioral and Social Sciences: Workshop Report - Institute of Medicine; Transportation Research Board; National Research Council (The National Academies Press, 2007)
From a public health perspective, motor vehicle crashes are among the most serious problems facing teenagers. Even after more than six months of being licensed to drive alone, teens are two to three times more likely to be in a fatal crash than are the more experienced drivers. Crash rates are significantly higher for male drivers, and young people in the United States are at greater risk of dying or being injured in an automobile than their peers around the world. In fact, in 2003 motor vehicle crashes was the leading cause of death for youth ages 16-20 in the United States. Understanding how and why teen motor vehicle crashes happen is key to developing countermeasures to reduce their number. Applying this understanding to the development of prevention strategies holds significant promise for improving safety but many of these efforts are thwarted by a lack of evidence as to which prevention strategies are most effective. Preventing Teen Motor Crashes presents data from a multidisciplinary group that shared information on emerging technology for studying, monitoring, and controlling driving behavior. The book provides an overview of the factual information that was presented, as well as the insights that emerged about the role researchers can play in reducing and preventing teen motor crashes.
Keywords: Transportation and Infrastructure; Behavioral and Social Sciences; Health and Medicine

Improving Evaluation of Anticrime Programs - National Research Council (The National Academies Press, 2005)
Although billions of dollars have been spent on crime prevention and control programs during the past decade, scientifically strong impact evaluations of these programs are uncommon in the context of the overall number of programs that have received funding. Improving Evaluation of Anticrime Programs is designed as a working guide for agencies and organizations responsible for program evaluation, for researchers who must design scientifically credible evaluations of government and privately sponsored programs, and for policy officials who are investing more and more in the concept of evidence-based policy to guide their decisions in crucial areas of crime prevention and control.
Keywords: Behavioral and Social Sciences

A Population Health Perspective on Middle School Success: Activities, Programs, and Policies: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On December 5, 2019, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the factors that affect the health and well-being of middle-school-aged adolescents. The workshop included presentations on the risk factors of poor physical, social, and emotional outcomes and their prevalence; the identification of resilience factors; current policies and programs designed to support middle school success and address issues of equity and financing as they apply to these; and how the health and human services sectors can support and align with the education sector to promote health and well-being in middle school. This publication summarizes the presentations and discussions that took place during the workshop.
Keywords: Health and Medicine

The Private Sector as a Catalyst for Health Equity and a Vibrant Economy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
A critical component of the nation’s economic vitality is ensuring that all Americans can contribute and prosper. Such contributions presuppose an intentional focus on achieving the highest levels of health possible, which requires that conditions in communities, schools workplaces, and other settings promote health and address the social determinants of health for all community members. Many organizations, in both the private and public sectors, have been establishing partnerships to further healthy workplaces and health equity in general. Many are taking the lead in producing economic growth that is inclusive and responsive to the nation’s diverse needs and populations. Increasingly, private–public partnerships are emerging as ways of doing business. Additionally, a variety of new developments in health, health care, and community benefits obligations that are part of the Affordable Care Act have contributed to this interest in economic growth and health and in the creation of new partnerships. To examine past successes and future opportunities, the National Academies of Sciences, Engineering, and Medicine held a workshop in November 2015. The workshop focused on the potential of the private sector to produce a triple bottom line: economic opportunity (including workforce development) and growth, healthy work and community environments, and improved employee health. At the same time, participants looked beyond the private sector to public–private partnerships and to public-sector actions that combine opportunities for economic growth and good health for all. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Conference on Human Health and Global Climate Change: Summary of the Proceedings (The National Academies Press, 1996)
Keywords: Environment and Environmental Studies

Family-Focused Interventions to Prevent Substance Use Disorders in Adolescence: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Adolescence is a crucial period of life for the prevention of substance use disorders. Research has shown that early intervention can significantly reduce rates of substance use disorder in adulthood. To learn more about effective family-focused interventions in primary care settings for preventing substance use disorder, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on May 5-6, 2022. The proceedings from that workshop explores existing efforts to incorporate family-focused interventions into state health care policies. It also examines barriers to implementing such interventions as well as lessons learned from successful efforts to scale up these interventions.
Keywords: Behavioral and Social Sciences

Contagion of Violence: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
The past 25 years have seen a major paradigm shift in the field of violence prevention, from the assumption that violence is inevitable to the recognition that violence is preventable. Part of this shift has occurred in thinking about why violence occurs, and where intervention points might lie. In exploring the occurrence of violence, researchers have recognized the tendency for violent acts to cluster, to spread from place to place, and to mutate from one type to another. Furthermore, violent acts are often preceded or followed by other violent acts. In the field of public health, such a process has also been seen in the infectious disease model, in which an agent or vector initiates a specific biological pathway leading to symptoms of disease and infectivity. The agent transmits from individual to individual, and levels of the disease in the population above the baseline constitute an epidemic. Although violence does not have a readily observable biological agent as an initiator, it can follow similar epidemiological pathways. On April 30-May 1, 2012, the Institute of Medicine (IOM) Forum on Global Violence Prevention convened a workshop to explore the contagious nature of violence. Part of the Forum's mandate is to engage in multisectoral, multidirectional dialogue that explores crosscutting, evidence-based approaches to violence prevention, and the Forum has convened four workshops to this point exploring various elements of violence prevention. The workshops are designed to examine such approaches from multiple perspectives and at multiple levels of society. In particular, the workshop on the contagion of violence focused on exploring the epidemiology of the contagion, describing possible processes and mechanisms by which violence is transmitted, examining how contextual factors mitigate or exacerbate the issue. Contagion of Violence: Workshop Summary covers the major topics that arose during the 2-day workshop. It is organized by important elements of the infectious disease model so as to present the contagion of violence in a larger context and in a more compelling and comprehensive way.
Keywords: Health and Medicine

For the Public's Health: Investing in a Healthier Future - Institute of Medicine (The National Academies Press, 2012)
The Robert Wood Johnson Foundation asked the Institute of Medicine (IOM) to examine three topics in relation to public health: measurement, the law, and funding. IOM prepared a three report series—one report on each topic—that contains actionable recommendations for public health agencies and other stakeholders with roles in the health of the U.S. population. For the Public's Health: Investing in a Healthier Future, the final book inthe series, assesses the financial challenges facing the governmental public health infrastructure. The book provides recommendations about what is needed for stable and sustainable funding, and for its optimal use by public health agencies. Building on the other two volumes in the series, this book makes the argument that adequate and sustainable funding for public health is necessary to enable public health departments across the country to inform and mobilize action on the determinants of health, to play other key roles in protecting and promoting health, and to prepare for a range of potential threats to population health. The final book in the For the Public's Health series will be useful to federal, state, and local governments; public health agencies; clinical care organizations; and community-based organizations.
Keywords: Health and Medicine

Plan for a Short-Term Evaluation of PEPFAR Implementation: Letter Report #1 - Institute of Medicine (The National Academies Press, 2006)
Keywords: Health and Medicine

Exploring Opportunities for Collaboration Between Health and Education to Improve Population Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Research based on decades of experience in the developing world has identified educational status, especially the status of the mother, as a major predictor of health outcomes and that the literature indicates that the gradient in health outcomes by educational attainment has steepened over the last four decades across the United States. Since the 1990s, while the average life expectancy in the United States has been steadily increasing, life expectancy has actually decreased for people without a high school education, especially white women. To understand the complex relationship between education and health and how this understanding could inform our nation's investments and policies, the Institute of Medicine Roundtable on Population Health Improvement held a public workshop in Washington, DC, on June 5, 2014. This workshop, which featured presentations and extensive discussion periods, also explored how the health and education sectors can work together more effectively to achieve improvements in both health status and educational achievement. This report summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine

Strategies to Protect the Health of Deployed U.S. Forces: Medical Surveillance, Record Keeping, and Risk Reduction - Institute of Medicine (The National Academies Press, 1999)
Nine years after Operations Desert Shield and Desert Storm (the Gulf War) ended in June 1991, uncertainty and questions remain about illnesses reported in a substantial percentage of the 697,000 service members who were deployed. Even though it was a short conflict with very few battle casualties or immediately recognized disease or non-battle injuries, the events of the Gulf War and the experiences of the ensuing years have made clear many potentially instructive aspects of the deployment and its hazards. Since the Gulf War, several other large deployments have also occurred, including deployments to Haiti and Somalia. Major deployments to Bosnia, Southwest Asia, and, most recently, Kosovo are ongoing as this report is written. This report draws on lessons learned from some of these deployments to consider strategies to protect the health of troops in future deployments. In the spring of 1996, Deputy Secretary of Defense John White met with leadership of the National Research Council and the Institute of Medicine to explore the prospect of an independent, proactive effort to learn from lessons of the Gulf War and to develop a strategy to better protect the health of troops in future deployments.
Keywords: Health and Medicine

Reducing Risks for Mental Disorders: Frontiers for Preventive Intervention Research - Institute of Medicine (The National Academies Press, 1994)
The understanding of how to reduce risk factors for mental disorders has expanded remarkably as a result of recent scientific advances. This study, mandated by Congress, reviews those advances in the context of current research and provides a targeted definition of prevention and a conceptual framework that emphasizes risk reduction. Highlighting opportunities for and barriers to interventions, the book draws on successful models for the prevention of cardiovascular disease, injuries, and smoking. In addition, it reviews the risk factors associated with Alzheimer's disease, schizophrenia, alcohol abuse and dependence, depressive disorders, and conduct disorders and evaluates current illustrative prevention programs. The models and examination provide a framework for the design, application, and evaluation of interventions intended to prevent mental disorders and the transfer of knowledge about prevention from research to clinical practice. The book presents a focused research agenda, with recommendations on how to develop effective intervention programs, create a cadre of prevention researchers, and improve coordination among federal agencies.
Keywords: Health and Medicine

Reducing the Burden of Injury: Advancing Prevention and Treatment - Institute of Medicine (The National Academies Press, 1999)
Injuries are the leading cause of death and disability among people under age 35 in the United States. Despite great strides in injury prevention over the decades, injuries result in 150,000 deaths, 2.6 million hospitalizations, and 36 million visits to the emergency room each year. Reducing the Burden of Injury describes the cost and magnitude of the injury problem in America and looks critically at the current response by the public and private sectors, including: Data and surveillance needs. Research priorities. Trauma care systems development. Infrastructure support, including training for injury professionals. Firearm safety. Coordination among federal agencies. The authors define the field of injury and establish boundaries for the field regarding intentional injuries. This book highlights the crosscutting nature of the injury field, identifies opportunities to leverage resources and expertise of the numerous parties involved, and discusses issues regarding leadership at the federal level.
Keywords: Health and Medicine

Public Policy Approaches to Violence Prevention: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The National Academies of Sciences, Engineering, and Medicine held a workshop on December 1–2, 2016, with the aim of illuminating the ways in which violence prevention practitioners can effectively share their evidenced-based research findings with policy makers in order to positively affect and amplify violence prevention efforts. The workshop explored this topic through three lenses: (1) economics and costing, (2) research and evidence, and (3) effective communications and messaging. This approach underscored the fact that violence prevention is a complex and multi-faceted issue that requires an interdisciplinary approach. This 2-day workshop brought together a diverse group of experts from various domains and backgrounds to foster multi-sectoral dialogues on the topic. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Methodological Challenges in Biomedical HIV Prevention Trials - Institute of Medicine (The National Academies Press, 2008)
The number of people infected with HIV or living with AIDS is increasing at unprecedented rates as various scientists, organizations, and institutions search for innovative solutions to combating and preventing the disease. At the request of the Bill & Melinda Gates Foundation, Methodological Challenges in Biomedical HIV Prevention Trials addresses methodological challenges in late-stage nonvaccine biomedical HIV prevention trials with a specific focus on microbicide and pre-exposure prophylaxis trials. This book recommends a number of ways to improve the design, monitoring, and analysis of late-stage clinical trials that evaluate nonvaccine biomedical interventions. The objectives include identifying a beneficial method of intervention, enhancing quantification of the impact, properly assessing the effects of using such an intervention, and reducing biases that can lead to false positive trial results. According to Methodological Challenges in Biomedical HIV Prevention Trials, the need to identify a range of effective, practical, and affordable preventive strategies is critical. Although a large number of promising new HIV prevention strategies and products are currently being tested in late-stage clinical trials, these trials face a myriad of methodological challenges that slow the pace of research and limit the ability to identify and fully evaluate effective biomedical interventions.
Keywords: Health and Medicine

Review of the HIVNET 012 Perinatal HIV Prevention Study - Institute of Medicine (The National Academies Press, 2005)
Mother-to-child transmission of HIV-1 afflicts hundreds of thousands of children every year, especially in parts of the world such as sub-Saharan Africa, where HIV infection is prevalent and resources are limited. This tragic reality has spurred researchers to search for an effective, safe, and inexpensive treatment that could reduce the risk of perinatal HIV transmission. The HIVNET 012 trial was designed to provide preliminary information on the comparative safety and efficacy of two relatively simple and inexpensive short courses of oral antiretroviral treatment likely to be feasible in resource-limited settings. The resulting report identified some problems with procedures and documentation, but concluded that these issues did not compromise the results of the study. However, these issues have led to public scrutiny and continued controversy. Review of the HIVNET 012 Perinatal HIV Prevention Study critically and objectively evaluates the study's design and conduct, and assesses the impact of the initial procedural issues on the validity of the overall findings and conclusions of the trial.
Keywords: Health and Medicine

Older Commercial Drivers: Do They Pose a Safety Risk? - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 18: Older Commercial Drivers: Do They Pose a Safety Risk? explores age-related changes in the basic functional abilities needed to drive safely. The report is designed to help assist industry and labor practitioners in promoting safer commercial operations.
Keywords: Transportation and Infrastructure

Integrating Responses at the Intersection of Opioid Use Disorder and Infectious Disease Epidemics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
According to the Centers for Disease Control and Prevention (CDC), 115 Americans die each day from an opioid overdose, which averages one death every 12.5 minutes. Between 1999 and 2016, the number of drug overdoses catapulted by 300 percent, with injection drug use increasing by 93 percent between 2004 and 2014 and opioid-related hospital admissions increasing by 58 percent over the past decade. And an inexorable sequela of the opioid epidemic is the spread of infectious diseases. To address these infectious disease consequences of the opioid crisis, a public workshop titled Integrating Infectious Disease Considerations with Response to the Opioid Epidemic was convened on March 12 and 13, 2018, by the National Academies of Sciences, Engineering, and Medicine. Participants discussed strategies to prevent and treat infections in people who inject drugs, especially ways to work efficiently though the existing public health and medical systems. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Proactive Policing: Effects on Crime and Communities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Proactive policing, as a strategic approach used by police agencies to prevent crime, is a relatively new phenomenon in the United States. It developed from a crisis in confidence in policing that began to emerge in the 1960s because of social unrest, rising crime rates, and growing skepticism regarding the effectiveness of standard approaches to policing. In response, beginning in the 1980s and 1990s, innovative police practices and policies that took a more proactive approach began to develop. This report uses the term "proactive policing" to refer to all policing strategies that have as one of their goals the prevention or reduction of crime and disorder and that are not reactive in terms of focusing primarily on uncovering ongoing crime or on investigating or responding to crimes once they have occurred. Proactive policing is distinguished from the everyday decisions of police officers to be proactive in specific situations and instead refers to a strategic decision by police agencies to use proactive police responses in a programmatic way to reduce crime. Today, proactive policing strategies are used widely in the United States. They are not isolated programs used by a select group of agencies but rather a set of ideas that have spread across the landscape of policing. Proactive Policing reviews the evidence and discusses the data and methodological gaps on: (1) the effects of different forms of proactive policing on crime; (2) whether they are applied in a discriminatory manner; (3) whether they are being used in a legal fashion; and (4) community reaction. This report offers a comprehensive evaluation of proactive policing that includes not only its crime prevention impacts but also its broader implications for justice and U.S. communities.
Keywords: Behavioral and Social Sciences

Leadership Commitments to Improve Value in Health Care: Finding Common Ground: Workshop Summary - Institute of Medicine (The National Academies Press, 2009)
This volume reports on discussions among multiple stakeholders about ways they might help transform health care in the United States. The U.S. healthcare system consists of a complex network of decentralized and loosely associated organizations, services, relationships, and participants. Each of the healthcare system's component sectors--patients, healthcare professionals, healthcare delivery organizations, healthcare product developers, clinical investigators and evaluators, regulators, insurers, employers and employees, and individuals involved in information technology--conducts activities that support a common goal: to improve patient health and wellbeing. Implicit in this goal is the commitment of each stakeholder group to contribute to the evidence base for health care, that is, to assist with the development and application of information about the efficacy, safety, effectiveness, value, and appropriateness of the health care delivered.
Keywords: Health and Medicine

Challenges in Adolescent Health Care: Workshop Report - National Research Council; Institute of Medicine (The National Academies Press, 2007)
Several positive and negative lifelong behaviors are established during adolescence including diet and exercise, sexual conduct, practices related to oral health, smoking, drinking, and the use if legal and illegal substances. The complex issues that adolescents deal with on a daily basis can turn into health problems that persist throughout adulthood. Unfortunately the adolescents who are frequently the most disconnected from routine health care services - those who lack insurance and family support - are often those at greatest risk for multiple and chronic health problems. Therefore, those that are responsible for delivering health care services to adolescents must address the health conditions that require immediate attention while preparing young people to adopt practices that can help improve their future health status and prevent unhealthy behaviors. Challenges in Adolescent Health Care studies adolescent health care in the United States, highlights critical health care needs, and identifies service models and components of care that may strengthen and improve health care services, settings, and systems for adolescents. The book explores the nature of adolescent challenges and how they reflect larger societal issues such as poverty, crime and the prevalence of violence. These issues, in addition to lack of comprehensive health coverage, dysfunctional families and the lack of support systems, make providing adequate health care incredibly challenging. Challenges in Adolescent Health Care defines high-quality health care, identifies the strengths and weaknesses of various service models and explores various training programs. The book recommends that health care providers must be sensitive to socioeconomic factors and incorporate health care in a broad array of settings including schools, neighborhoods and community centers.
Keywords: Health and Medicine

Promoting Health Literacy to Encourage Prevention and Wellness: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Health literacy has been shown to affect health outcomes. The use of preventive services improves health and prevents costly health care expenditures. Several studies have found that health literacy makes a difference in the extent to which populations use preventive services. On September 15, 2009, the Institute of Medicine Roundtable on Health Literacy held a workshop to explore approaches to integrate health literacy into primary and secondary prevention. Promoting Health Literacy to Encourage Prevention and Wellness serves as a factual account of the discussion that took place at the workshop. The report describes the inclusion of health literacy into public health prevention programs at the national, state, and local levels; reviews how insurance companies factor health literacy into their prevention programs; and discusses industry contributions to providing health literate primary and secondary prevention.
Keywords: Health and Medicine

Estimating the Contributions of Lifestyle-Related Factors to Preventable Death: A Workshop Summary - Institute of Medicine (The National Academies Press, 2005)
This report is the summary of a workshop held by The Institute of Medicine (IOM) of the National Academy of Science December 13-14, 2004 to estimate the contributions of lifestyle-related factors to preventable death. The summary of this workshop includes presentations from experts in statistical design, epidemiology, quality-of-life measures, communication, and public policy and discussions among the participants. Panels of experts addressed the following topics: methodological issues when estimating the public health burden of lifestyle factors; estimating "attributable risk" in practice; alternative ways of measuring the health burden; and public policy issues.
Keywords: Health and Medicine

Integrating Large-Scale Genomic Information into Clinical Practice: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The initial sequencing of the human genome, carried out by an international group of experts, took 13 years and $2.7 billion to complete. In the decade since that achievement, sequencing technology has evolved at such a rapid pace that today a consumer can have his or her entire genome sequenced by a single company in a matter of days for less than $10,000, though the addition of interpretation may extend this timeframe. Given the rapid technological advances, the potential effect on the lives of patients, and the increasing use of genomic information in clinical care, it is important to address how genomics data can be integrated into the clinical setting. Genetic tests are already used to assess the risk of breast and ovarian cancers, to diagnose recessive diseases such as cystic fibrosis, to determine drug dosages based on individual patient metabolism, and to identify therapeutic options for treating lung and breast tumors, melanoma, and leukemia. With these issues in mind and considering the potential impact that genomics information can have on the prevention, diagnosis, and treatment of disease, the Roundtable on Translating Genomic-Based Research for Health hosted a workshop on July 19, 2011, to highlight and identify the challenges and opportunities in integrating large-scale genomic information into clinical practice. Integrating Large-Scale Genomic Information into Clinical Practice summarizes the speaker presentations and the discussions that followed them. This report focuses on several key topics, including the analysis, interpretation, and delivery of genomic information plus workforce, ethical, and legal issues.
Keywords: Health and Medicine

Security 101: A Physical Security Primer for Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 525: Surface Transportation Security, Volume 14, Security 101: A Physical Security Primer for Transportation Agencies is designed to provide transportation managers and employees with an introductory-level reference document to enhance their working knowledge of security concepts, guidelines, definitions, and standards.NCHRP Report 525: Surface Transportation Security is a series in which relevant information is assembled into single, concise volumes—each pertaining to a specific security problem and closely related issues. The volumes focus on the concerns that transportation agencies are addressing when developing programs in response to the terrorist attacks of September 11, 2001, and the anthrax attacks that followed. Future volumes of the report will be issued as they are completed.
Keywords: Transportation and Infrastructure

Exploring Equity in Multisector Community Health Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Building on previous National Academies of Sciences, Engineering, and Medicine workshops that explored how safe and healthy communities are a necessary component of health equity and efforts to improve population health, the Roundtable on Population Health Improvement wanted to explore how a variety of community-based organizations came together to achieve population health. To do so, the roundtable hosted a workshop in Oakland, California, on December 8, 2016, to explore multisector health partnerships that engage residents, reduce health disparities, and improve health and well-being. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Understanding and Overcoming the Challenge of Obesity and Overweight in the Armed Forces: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Obesity and overweight pose significant challenges to the armed forces in the United States, affecting service members (including active duty, guard, and reserve components), veterans, retirees, and their families and communities. The consequences of obesity and overweight in the armed forces influence various aspects of its operations that are critical to national security. On May 7, 2018, the National Academies of Sciences, Engineering, and Medicine, held a workshop titled “Understanding and Overcoming the Challenge of Obesity and Overweight in the Armed Forces.” Speakers examined how obesity and overweight are measured in the armed forces and how they affect recruitment, retention, resilience, and readiness; discussed service-specific issues related to these problems and highlighted innovative strategies to address them through improved nutrition, physical activity, and stress management; and offered perspectives from outside of the armed forces on approaches to prevent and treat obesity. They also discussed the challenges and opportunities related to overcoming the concerns posed by obesity and overweight in the armed forces, military families, and their communities, including potential cross-sector opportunities. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Investing in Interventions That Address Non-Medical, Health-Related Social Needs: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
With U.S. health care costs projected to grow at an average rate of 5.5 percent per year from 2018 to 2027, or 0.8 percentage points faster than the gross domestic product, and reach nearly $6.0 trillion per year by 2027, policy makers and a wide range of stakeholders are searching for plausible actions the nation can take to slow this rise and keep health expenditures from consuming an ever greater portion of U.S. economic output. While health care services are essential to heath, there is growing recognition that social determinants of health are important influences on population health. Supporting this idea are estimates that while health care accounts for some 10 to 20 percent of the determinants of health, socioeconomic factors and factors related to the physical environment are estimated to account for up to 50 percent of the determinants of health. Challenges related to the social determinants of health at the individual level include housing insecurity and poor housing quality, food insecurity, limitations in access to transportation, and lack of social support. These social needs affect access to care and health care utilization as well as health outcomes. Health care systems have begun exploring ways to address non-medical, health-related social needs as a way to reduce health care costs. To explore the potential effect of addressing non-medical health-related social needs on improving population health and reducing health care spending in a value-driven health care delivery system, the National Academies of Science, Engineering, and Medicine held a full-day public workshop titled Investing in Interventions that Address Non-Medical, Health-Related Social Needs on April 26, 2019, in Washington, DC. The objectives of the workshop were to explore effective practices and the supporting evidence base for addressing the non-medical health-related social needs of individuals, such as housing and food insecurities; review assessments of return on investment (ROI) for payers, healthy systems, and communities; and identify gaps and opportunities for research and steps that could help to further the understanding of the ROI on addressing non-medical health-related social needs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Evaluating the Effectiveness of Interventions to Prevent and Address Sexual Harassment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Rising awareness of and increased attention to sexual harassment has resulted in momentum to implement sexual harassment prevention efforts in higher education institutions. Work on preventing sexual harassment is an area that has recently garnered a lot of attention, especially around education and programs that go beyond the standard anti-sexual harassment trainings often used to comply with legal requirements. On April 20-21, 2021, the National Academies of Sciences, Engineering, and Medicine hosted the workshop Developing Evaluation Metrics for Sexual Harassment Prevention Efforts. The workshop explored approaches and strategies for evaluating and measuring the effectiveness of sexual harassment interventions being implemented at higher education institutions and research and training sites, in order to assist institutions in transforming promising ideas into evidence-based best practices. Workshop participants also addressed methods, metrics, and measures that could be used to evaluate sexual harassment prevention efforts that lead to change in the organizational climate and culture and/or a change in behavior among community members. This publication summarizes the presentations and discussion of the workshop.
Keywords: Policy for Science and Technology

Reducing Litter on Roadsides - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 394: Reducing Litter on Roadsides explores the state of the practice in reducing roadside litter as it involves state departments of transportation (DOTs). The report provides information concerning the prevention and removal of roadside litter, unfulfilled needs, knowledge gaps, and underperforming activities. It covers enforcement, education, awareness, and engineering methods for both litter prevention and collection.
Keywords: Transportation and Infrastructure

Preventing Bullying Through Science, Policy, and Practice - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Bullying has long been tolerated as a rite of passage among children and adolescents. There is an implication that individuals who are bullied must have "asked for" this type of treatment, or deserved it. Sometimes, even the child who is bullied begins to internalize this idea. For many years, there has been a general acceptance and collective shrug when it comes to a child or adolescent with greater social capital or power pushing around a child perceived as subordinate. But bullying is not developmentally appropriate; it should not be considered a normal part of the typical social grouping that occurs throughout a child's life. Although bullying behavior endures through generations, the milieu is changing. Historically, bulling has occurred at school, the physical setting in which most of childhood is centered and the primary source for peer group formation. In recent years, however, the physical setting is not the only place bullying is occurring. Technology allows for an entirely new type of digital electronic aggression, cyberbullying, which takes place through chat rooms, instant messaging, social media, and other forms of digital electronic communication. Composition of peer groups, shifting demographics, changing societal norms, and modern technology are contextual factors that must be considered to understand and effectively react to bullying in the United States. Youth are embedded in multiple contexts and each of these contexts interacts with individual characteristics of youth in ways that either exacerbate or attenuate the association between these individual characteristics and bullying perpetration or victimization. Recognizing that bullying behavior is a major public health problem that demands the concerted and coordinated time and attention of parents, educators and school administrators, health care providers, policy makers, families, and others concerned with the care of children, this report evaluates the state of the science on biological and psychosocial consequences of peer victimization and the risk and protective factors that either increase or decrease peer victimization behavior and consequences.
Keywords: Behavioral and Social Sciences

Population Health in Challenging Times: Insights from Key Domains: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The year 2020 presented extraordinary challenges to organizations working to improve population health - from public health agencies at all levels of government to health systems to community-based non-profit organizations responding to health-related social needs. To improve understanding of how different domains in the population health field are responding to and being changed by two major crises (racial injustice and the COVID-19 pandemic), the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine held a workshop from September 21-24, 2020, titled Population Health in Challenging Times: Insights from Key Domains. The workshop had sessions organized by themes: academic public health and population health; the social sector; health care, governmental public health; philanthropy; and cross-sector work. Each panel discussion highlighted difficulties and opportunities, both internal to the respective institutions and sectors, and at the interface with peers and partners, especially communities. This publication summarizes the presentations and panel discussions from the workshop.
Keywords: Health and Medicine

The National Cancer Policy Summit: Opportunities and Challenges in Cancer Research and Care - Institute of Medicine (The National Academies Press, 2011)
Many ongoing changes are likely to have an impact on cancer research and care. For example, technological advances are rapidly changing the way cancer research is conducted, and the recently passed healthcare reform legislation has many implications for cancer care. Technological advances are altering the way cancer research is conducted and cancer care is delivered, and the recently passed healthcare reform legislation has many implications for cancer care. There is a growing emphasis on molecularly targeted therapies, information technology (IT), and patient-centered care, and clinical cancer research has become a global endeavor. At the same time, there are concerns about shrinking research budgets and escalating costs of cancer care. Considering such changes, the National Cancer Policy Forum (NCPF) of the Institute of Medicine held a National Cancer Policy Summit on October 25, 2010. The Summit convened key leaders in the cancer community to identify and discuss the most pressing policy issues in cancer research and cancer care. The National Cancer Policy Summit: Opportunities and Challenges in Cancer Research and Care is a summary of the summit. The report explores policy issues related to cancer research, the implementation of healthcare reform, delivery of cancer care, and cancer control and public health needs. Expert participants suggested many potential actions to provide patient-centered cancer care, to foster more collaboration, and to achieve other goals to improve research and care.
Keywords: Health and Medicine

Clinical Preventive Services for Women: Closing the Gaps - Institute of Medicine (The National Academies Press, 2011)
Women suffer disproportionate rates of chronic disease and disability from some conditions, and often have high out-of-pocket health care costs. The passage of the Patient Protection and Affordable Care Act of 2010 (ACA) provides the United States with an opportunity to reduce existing health disparities by providing an unprecedented level of population health care coverage. The expansion of coverage to millions of uninsured Americans and the new standards for coverage of preventive services that are included in the ACA can potentially improve the health and well-being of individuals across the United States. Women in particular stand to benefit from these additional preventive health services. Clinical Preventive Services for Women reviews the preventive services that are important to women's health and well-being. It recommends that eight preventive health services for women be added to the services that health plans will cover at no cost. The recommendations are based on a review of existing guidelines and an assessment of the evidence on the effectiveness of different preventive services. The services include improved screening for cervical cancer, sexually transmitted infections, and gestational diabetes; a fuller range of contraceptive education, counseling, methods, and services; services for pregnant women; at least one well-woman preventive care visit annually; and screening and counseling for interpersonal and domestic violence, among others. Clinical Preventive Services for Women identifies critical gaps in preventive services for women as well as measures that will further ensure optimal health and well-being. It can serve as a comprehensive guide for federal government agencies, including the Department of Health and Human Services and the Center for Disease Control and Prevention; state and local government agencies; policy makers; health care professionals; caregivers, and researchers.
Keywords: Health and Medicine

Vaccines Against Malaria - Institute of Medicine (The National Academies Press, 1996)
Keywords: Health and Medicine

Sustainable Agriculture Research and Education in the Field: A Proceedings - National Research Council (The National Academies Press, 1991)
Interest is growing in sustainable agriculture, which involves the use of productive and profitable farming practices that take advantage of natural biological processes to conserve resources, reduce inputs, protect the environment, and enhance public health. Continuing research is helping to demonstrate the ways that many factors—economics, biology, policy, and tradition—interact in sustainable agriculture systems. This book contains the proceedings of a workshop on the findings of a broad range of research projects funded by the U.S. Department of Agriculture. The areas of study, such as integrated pest management, alternative cropping and tillage systems, and comparisons with more conventional approaches, are essential to developing and adopting profitable and sustainable farming systems.
Keywords: Agriculture

Violence Prevention in Low- and Middle-Income Countries: Finding a Place on the Global Agenda: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
The current state of science in violence prevention reveals progress, promise, and a number of remaining challenges. In order to fully examine the issue of global violence prevention, the Institute of Medicine in collaboration with Global Violence Prevention Advocacy, convened a workshop and released the workshop summary entitled, Violence Prevention in Low-and Middle-Income Countries. The workshop brought together participants with a wide array of expertise in fields related to health, criminal justice, public policy, and economic development, to study and articulate specific opportunities for the U.S. government and other leaders with resources to more effectively support programming for prevention of the many types of violence. Participants highlighted the need for the timely development of an integrated, science-based approach and agenda to support research, clinical practice, program development, policy analysis, and advocacy for violence prevention.
Keywords: Behavioral and Social Sciences; Health and Medicine

Global Infectious Disease Surveillance and Detection: Assessing the Challenges–Finding Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
Early detection is essential to the control of emerging, reemerging, and novel infectious diseases, whether naturally occurring or intentionally introduced. Containing the spread of such diseases in a profoundly interconnected world requires active vigilance for signs of an outbreak, rapid recognition of its presence, and diagnosis of its microbial cause, in addition to strategies and resources for an appropriate and efficient response. Although these actions are often viewed in terms of human public health, they also challenge the plant and animal health communities. Surveillance, defined as "the continual scrutiny of all aspects of occurrence and spread of a disease that are pertinent to effective control", involves the "systematic collection, analysis, interpretation, and dissemination of health data." Disease detection and diagnosis is the act of discovering a novel, emerging, or reemerging disease or disease event and identifying its cause. Diagnosis is "the cornerstone of effective disease control and prevention efforts, including surveillance." Disease surveillance and detection relies heavily on the astute individual: the clinician, veterinarian, plant pathologist, farmer, livestock manager, or agricultural extension agent who notices something unusual, atypical, or suspicious and brings this discovery in a timely way to the attention of an appropriate representative of human public health, veterinary medicine, or agriculture. Most developed countries have the ability to detect and diagnose human, animal, and plant diseases. Global Infectious Disease Surveillance and Detection: Assessing the Challenges—Finding Solutions, Workshop Summary is part of a 10 book series and summarizes the recommendations and presentations of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Reducing Underage Drinking: A Collective Responsibility - National Research Council; Institute of Medicine (The National Academies Press, 2004)
Alcohol use by young people is extremely dangerous - both to themselves and society at large. Underage alcohol use is associated with traffic fatalities, violence, unsafe sex, suicide, educational failure, and other problem behaviors that diminish the prospects of future success, as well as health risks – and the earlier teens start drinking, the greater the danger. Despite these serious concerns, the media continues to make drinking look attractive to youth, and it remains possible and even easy for teenagers to get access to alcohol. Why is this dangerous behavior so pervasive? What can be done to prevent it? What will work and who is responsible for making sure it happens? Reducing Underage Drinking addresses these questions and proposes a new way to combat underage alcohol use. It explores the ways in which may different individuals and groups contribute to the problem and how they can be enlisted to prevent it. Reducing Underage Drinking will serve as both a game plan and a call to arms for anyone with an investment in youth health and safety.
Keywords: Health and Medicine; Behavioral and Social Sciences

Identifying and Managing Veteran Suicide Risk: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On May 23, 2023, the National Academies of Sciences, Engineering, and Medicine Board on Behavioral, Cognitive, and Sensory Sciences hosted a workshop titled Current Practices and Challenges for Identifying and Managing Suicide Risk Among Veterans in Non-Department of Veterans Affairs (VA) Healthcare Systems to explore the landscape of veteran health care and suicide risk; consider strategies to identify veterans who receive their health care outside of the VHA; and identify best practices for suicide risk identification and care for VA-purchased care in community and at non-VA entities. This proceedings presents a summary of the presentation and discussion of the workshop.
Keywords: Health and Medicine

AIDS, Sexual Behavior, and Intravenous Drug Use - National Research Council (The National Academies Press, 1989)
The AIDS virus is spread by human behaviors enacted in a variety of social situations. In order to prevent further infection, we need to know more about these behaviors. This volume explores what is known about the number of people infected, risk-associated behaviors, facilitation of behavioral change, and barriers to more effective prevention efforts.
Keywords: Health and Medicine